Crosslinking of comb-shaped polymer anion exchange membranes via thiol–ene click chemistry. Issue 14 (29th February 2016) - Zhu, Liang; Zimudzi, Tawanda J.; Li, Nanwen; Pan, Jing; Lin, Bencai; Hickner, Michael A.
Abstract : To produce anion conductive and durable polymer electrolytes for alkaline fuel cell applications, a series of cross-linked quaternary ammonium functionalized poly(2, 6-dimethyl-1, 4-phenylene oxide)s with mass-based ion exchange capacities (IEC) ranging from 1.80 to 2.55 mmol g −1 were synthesized via thiol–ene click chemistry. Abstract : To produce anion conductive and durable polymer electrolytes for alkaline fuel cell applications, a series of cross-linked quaternary ammonium functionalized poly(2, 6-dimethyl-1, 4-phenylene oxide)s with mass-based ion exchange capacities (IEC) ranging from 1.80 to 2.55 mmol g −1 were synthesized via thiol–ene click chemistry. 1 H nuclear magnetic resonance (NMR) spectroscopy and Fourier transform infrared spectroscopy (FTIR) were used to confirm the chemical structure of the samples. From small angle X-ray scattering (SAXS), it was found that the cross-linked membranes developed microphase separation between the hydrophilic PPO backbone and the hydrophobic alkyl side chains. The ion conductivity, dimensional stability, and alkaline durability of the cross-linked membranes were evaluated. The hydroxide ion conductivity of the cross-linked samples reached 60 mS cm −1 in liquid water at room temperature. The chemical stabilities of the membranes were evaluated under severe, accelerated aging conditions and degradation was quantified by measuring the ionic conductivity changes during aging. The cross-linked membranes retained their relatively high ion conductivity and good mechanical properties in both 1 M and 4 M NaOH at 80 °C after 500 h. Attenuated total reflection (ATR) spectra were used to study the degradation pathways of the membranes, and it was determined that β-hydrogen (Hofmann) elimination was likely to be the major pathway for degradation in these membranes.